Solar Cell Powered PJU Light Installation by Utilizing Solar Energy - budiartono budiartono; Tri Lestariningsih; Budi Triono; Nur Asyik Hidayatullah; Husain Haryo Wicaksono (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
Kedungbunder Village is included in the southern part of Blitar. The socio-economic activities of the people in Kedungbunder mostly rely on agriculture. The huge potential is the fertile agricultural land and the availability of potential solar energy around the settlement, allowing solar energy to be utilized as public street lighting. Community service activities through the Community Partnership Program will be carried out in Kedungbunder Village, Sutojayan District, Blitar Regency with an emphasis on community empowerment through the use of solar energy with solar cells for street lighting installations. The result is public awareness related to the benefits of solar energy and the application of solar cell-powered PJU lamp technology as street lighting.